(3HZjI GdQGei TQM efXheI aj GdQei HGdfTGHs - (3WjHZG GdcHGTi GdjhfGfis ((3CMeO Hf eMeO Hf GdLgfi s)
(3ChdgG (B:s
(3CeG HYO aEf Gddg JYGdi deG aQV YdjfG Qei GdfTGH GdLRjd GdKhGH hGQJHGW GdNjd GdJi YbO ai fhGUjgG GdNjQ Edi jhe GdbjGeI s
(3BNQgG (B:s
(3ef jgO Gddg agh GdegJOi hef jVdd adf JLO dg hdjkG eQTOkG Je GdcJGH GdeHGQc HMeO Gddg hYhfg hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3Ydi GdeNWhW JhbjY GdSjO GdeQJVi GdMSjfi UGMH JGL GdYQhSs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs